COMPARISON OF WORD-FORMATION SYSTEMS IN ENGLISH AND RUSSIAN LANGUAGES (Conferencea, 2023)
The main types of morphological word formation are affixation, compounding and non-affixing method. To determine the typological differences in the field of affixation, numerical data are essential. V.D. Arapkin suggests following J. Grinberg and E.S. Kubryakova to calculate the index of affixal word formation according to the formula